Effectiveness of the Developed Video Compact Disc (VCD) in Knowledge Dissemination - Anuradha,; Singh, Archana Raj (Indian Journal of Extension Education, 2012)
The present study was planned to develop a video compact disc on post - harvest technology on food grains and disseminate knowledge to rural women of Rajasthan (India) on post- harvest technology of foodgrains. The study was conducted in randomly selected two villages, i.e. Bhukarka and Chainpura, of Nohar Panchayat Samiti (purposively selected) of Hanumangarh district. Samples of 50 farm women were selected (25 from each village). Pre-post experimental research design was used for the investigation. The study was carried out in two phases. Phase I: Development of video compact disc (VCD) on post-harvest technology of food grains and Phase II: Field testing of video compact disc (VCD) on post-harvest technology of food grains. The effectiveness of video program in terms of video quality, visual quality, presentation of message, content importance suitability and text was relatively high. The overall effectiveness of video compact disc was also high. Most of the farm women (86%) were in a medium level knowledge category with mean per cent score (29.38), followed by high-level knowledge category (12%) with (MPS 44.36) and low knowledge category (2%) with (MPS 22) in pre test. In post test, maximum number of farm women (94%) had medium knowledge with (MPS 73.77), followed by high knowledge category (4%) with (MPS 88.23) and low knowledge category (1%) with (MPS 58.22). Majority of farm women (76%) were in the category of a medium level knowledge gain with (MPS 45.70), followed by low knowledge category (14%) with (MPS 26.89) and high knowledge gain category (10%) with (MPS 58.23). The overall gain in knowledge through developed VCD was found to be statistically significant at 0.1%level of significance. Thus video program was very effective because the message was simple, familiar, understandable and real. The farm women had perceived and comprehend the message of video compact disc very well. The developed video compact disc was found effective in educating to farm women.
Keywords: Knowledge; post -harvest technology; Dissemination; Empowerment